2015
DOI: 10.1016/j.atmosenv.2015.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylamine as a major alkyl amine species in particles and cloud water: Observations in semi-arid and coastal regions

Abstract: Aerosol and cloud water measurements of dimethylamine (DMA), the most abundant amine in this study, were conducted in semi-arid (Tucson, Arizona) and marine (Nucleation in California Experiment, NiCE; central coast of California) areas. In both regions, DMA exhibits a unimodal aerosol mass size distribution with a dominant peak between 0.18 and 0.56 μm. Particulate DMA concentrations increase as a function of marine biogenic emissions, sulfate, BVOC emissions, and aerosol-phase water. Such data supports biogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 52 publications
2
100
0
Order By: Relevance
“…It is well known that ocean ecosystems emit DMS gas that subsequently oxidizes to form either methanesulfonic acid (MSA) or SO 2 , the latter of which can eventually form particulate SO 4 2‐ . SOA can also be formed in the MBL due to emissions of marine biogenic VOCs, including end products such as alkyl amines (Facchini, Decesari, et al, ; Youn et al, ) among others. It has also been hypothesized that increased organic compounds in the seawater translate into elevated organic aerosol emissions via bubble‐bursting processes.…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…It is well known that ocean ecosystems emit DMS gas that subsequently oxidizes to form either methanesulfonic acid (MSA) or SO 2 , the latter of which can eventually form particulate SO 4 2‐ . SOA can also be formed in the MBL due to emissions of marine biogenic VOCs, including end products such as alkyl amines (Facchini, Decesari, et al, ; Youn et al, ) among others. It has also been hypothesized that increased organic compounds in the seawater translate into elevated organic aerosol emissions via bubble‐bursting processes.…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…So far, this research has shown that amines may take part in aerosol chemistry in several ways. These include acid-base reactions to form aminium salts and dissolution in cloud droplets (owing to their high water solubility) where subsequent acid-base reactions can occur in the aqueous phase (e.g., Glasoe et al, 2015;Dawson et al, 2012;Erupe et al, 2011;Ge et al, 2011b;Jen et al, 2016Jen et al, , 2014Youn et al, 2015;Yu et al, 2012;Rehbein et al, 2011;Pankow, 2015). Amines compete with ammonia (NH 3 ) in neutralizing acidic aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…[]. Ammonium and SO 4 2− often exhibit the same mass size distribution with peaks in the accumulation mode, indicative of secondary formation via acid‐base chemistry [e.g., Maudlin et al ., ; Youn et al ., ]. Sources of NH 3 include livestock waste, fertilizer, biomass burning, and vehicular emissions [ Battye et al ., ].…”
Section: Discussionmentioning
confidence: 99%